2004
DOI: 10.1001/archinte.164.1.77
|View full text |Cite
|
Sign up to set email alerts
|

High Impact of Antiphospholipid Syndrome on Irreversible Organ Damage and Survival of Patients With Systemic Lupus Erythematosus

Abstract: Antiphospholipid syndrome with thrombotic manifestations is a major predictor of irreversible organ damage and death in patients with SLE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
146
0
6

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 207 publications
(163 citation statements)
references
References 26 publications
11
146
0
6
Order By: Relevance
“…Recent studies have also shown that the antiphospholipid syndrome with thrombotic complications in SLE is a major adverse factor for irreversible organ damage and survival (26). In large cohort studies, the lupus anticoagulant has been shown to be a significant risk factor for myocardial infarction (20) and stroke (27) in both Caucasian and non-Caucasian patients with SLE.…”
mentioning
confidence: 99%
“…Recent studies have also shown that the antiphospholipid syndrome with thrombotic complications in SLE is a major adverse factor for irreversible organ damage and survival (26). In large cohort studies, the lupus anticoagulant has been shown to be a significant risk factor for myocardial infarction (20) and stroke (27) in both Caucasian and non-Caucasian patients with SLE.…”
mentioning
confidence: 99%
“…3 The effect APS may exert on mortality, however, has been more rarely investigated. 11,12 There are studies which have associated survival with the age at the diagnosis of SLE. 3,5,[11][12][13] Being diagnosed after the age of 50 years has been associated with poor survival.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 There are studies which have associated survival with the age at the diagnosis of SLE. 3,5,[11][12][13] Being diagnosed after the age of 50 years has been associated with poor survival. 3 Ruiz-Irastorza et al 11 have identified older age at the time of diagnosis as an independent risk factor for mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although aPL increases the risk of vascular events and death in SLE (32)(33)(34)(35)(36), the role of aPL in the development of atherosclerosis in humans remains controversial (37,38). Antiphospholipid antibodies crossreact with antibodies against oxidized low-density lipoprotein (LDL) (39,40) and may enhance its uptake by macrophages (41), which represents the initial step of atherosclerotic plaque formation (42).…”
mentioning
confidence: 99%